Strategi Penghidupan Petani Hortikultura di Kota Tebing Tinggi - Rahmi, Wishlia; Prasetyo, Agus Subhan; rayoga, Kadhung P (JURNAL LITBANG PROVINSI JAWA TENGAH, 2024)
Horticultural farmers in Tebing Tinggi make farming their main job, but working as a farmer does not guarantee welfare in Tebing Tinggi. Livelihood strategies are various activities or efforts undertaken by individuals or households to meet their life needs for survival. Livelihood strategies are grouped into single and mixed strategies. Livelihood strategies are divided into five: human capital, natural capital, financial capital, physical capital, and social capital. Research locations were purposive in Tebing Tinggi City, North Sumatra Province. This study aimed to analyze the impact of the absence of collectors analyzing human capital, natural capital, financial capital, physical capital, and social capital of farmers and the livelihood strategies of horticultural farmers. This study's informants comprised 15 people, and ten informants tended to adopt a mixed livelihood strategy. The method used is a survey with a qualitative descriptive nature. The method of determining informants using snowball sampling. The study's results show that the impact of the absence of collectors for horticultural farmers is that their income decreases because they are now forced to limit the amount of harvest. A total of 10 informants implemented a mixed livelihood strategy, and five others implemented a single livelihood strategy. Owned capital consists of 5, namely human capital consisting of education level and labor allocation, physical capital consisting of houses and vehicles, natural capital consisting of agricultural land and livestock, financial capital consisting of savings and loans, and capital social services consisting of farmer groups and government agencies.